The international criminal responsibility of the individual - Pérez Sánchez-Cerro, José Luis (2023)
The lasting impact of the Rome Statute and the International Criminal Court (ICC), a crucial institution dedicated to combating impunity globally, is worth remembering. By exploring the evolution of individual criminal responsibility in international law, with special attention to the renowned Nuremberg and Tokyo Trials after World War II, it highlights the current urgency of a permanent international criminal tribunal, embodied by the Rome Statute of 1998 and the establishment of the ICC in 2002. Therefore, the article focuses on the Court’s jurisdiction over individuals and key principles, such as the responsibility of states to prosecute or extradite, providing an understandable perspective on the Court’s authority in international justice.